Pricing futures and real options with a liquidity factor: theory and evidence - Ding, Shusheng (2016)
Liquidity is one of the most intensively topics researched in financial economics for the last decade. Against this backdrop, this thesis attempts to address issue of liquidity in derivative markets and derivative models.